2011
DOI: 10.1016/j.cognition.2011.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Grasping the concept of personal property

Abstract: a b s t r a c tThe concept of property is integral to personal and societal development, yet understanding of the cognitive basis of ownership is limited. Objects are the most basic form of property, so our physical interactions with owned objects may elucidate nuanced aspects of ownership. We gave participants a coffee mug to decorate, use and keep. The experimenter also designed a mug of her own. In Experiment 1, participants performed natural lifting actions with each mug. Participants lifted the Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
105
4
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(116 citation statements)
references
References 34 publications
6
105
4
1
Order By: Relevance
“…First, it was the experimenter who was always manipulating the objects. Second, as shown recently [36], property also interacts with our manipulations with objects in the space affecting the proximity of our actions. Finally, the lack of control in the speed at which the experimenter moved the objects towards the participants as well as variable RT to participants' instruction to stop may have also influenced the reaching estimates.…”
Section: Experiments 2: Digital Scenariomentioning
confidence: 67%
See 1 more Smart Citation
“…First, it was the experimenter who was always manipulating the objects. Second, as shown recently [36], property also interacts with our manipulations with objects in the space affecting the proximity of our actions. Finally, the lack of control in the speed at which the experimenter moved the objects towards the participants as well as variable RT to participants' instruction to stop may have also influenced the reaching estimates.…”
Section: Experiments 2: Digital Scenariomentioning
confidence: 67%
“…Likewise, motor actions modulate subsequent affective evaluations of the objects involved [34]; see [35] for a review. In a recent study, Constable, Kritikos and Bayliss [36] demonstrated that other psychological concepts like ownership may also play important roles during object-oriented actions. Finally, egocentric distance estimation seems to be affected by the desirability of objects [37].…”
Section: Introductionmentioning
confidence: 99%
“…Ownership is an important aspect of our representation of objects, and has wide-ranging effects on people's thinking about objects. For example, it affects how accurately objects and their locations are remembered, how they are physically handled, and even how people refer to them (e.g., Constable, Kritikos, & Bayliss, 2011;Coventry, …”
mentioning
confidence: 99%
“…In the case of ownership, self-owned objects enjoy elevated importance with regards to a number of psychological variables including attention (Turk et al, 2011) and memory (Cunningham, Turk, MacDonald & Macrae, 2008). Interestingly, ownership has also been shown to influence physical interactions with objects when individuals act alone: 1) actors reach lower peak accelerations when lifting someone else's object than when they lift their own object; and 2) actors' movements are consistent with a general reticence to interact with other people's objects (Constable, Kritikos, & Bayliss, 2011;Constable, Kritikos, Lipp Running head: OBJECT OWNERSHIP AND FACILITATORY BEHAHAVIOR 4 & Bayliss, 2014). These effects reflect important biases in attachment, preference, and perhaps learned motor programs (see Constable et al, 2014 for a discussion) that alter the manner in which people plan and produce actions toward objects.…”
Section: Ownership Status Influences the Degree Of Joint Facilitatorymentioning
confidence: 99%